The Flipped Classroom: Enhancing Students’ Learning in Teaching Calculus - Cablas, Engr. Joven C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Educators have faced difficulties in efficiently teaching within the present regular school system. State, university, and college officials have been pressed to shift from face-to-face classes to teaching methodologies that address the constraints of the traditional method of instruction. Digital natives, also known as modern educators, spend more class time connecting with students and filling learning gaps with technological tools. To assist the development of learning, they began using interactive movies, interactive in-class activities, and video conference technologies. This includes utilizing a Flipped Classroom. This effort determined the effect of employing the flipped classroom technique in teaching Calculus in order to solve the issues experienced in teaching Mathematics during the new normal. The study included 20 first-year Electrical and Mechanical Engineering students who were enrolled in the second semester of the academic year 2019-2020 students whose problem-solving abilities and Calculus ability were assessed using a researcher-created test. A One-Group Pretest-Posttest Experimental Design was used by the researcher. The experimental study used four sessions of video instruction during pandemic season before the online class interactions. The researchers feel that flipped classrooms are appropriate for teaching Calculus since slow learners can watch the video repeatedly until they understand the material. As a result, assignments in the classroom focused on collaborative learning. As seen by the posttest findings, the use of the flipped classroom technique helped students enhance their problem-solving skills and mastery of solving Calculus issues. Thus, the flipped classroom method was found to be helpful in improving students' problem-solving skills and performance in Calculus among Guimaras State College's College of Engineering and Industrial Technology students.